Introducing comparative immunology through the lens of scaling biology - Downs, Cynthia J.; Elliott, Samantha L. (Frontiers in Education, 2025)
In most undergraduate programs, immunology is relegated to a few weeks of microbiology or human anatomy courses, or rarely offered as a dedicated topics course. As such, we feel it is essential to consider new approaches to introduce undergraduate students to immunological concepts. Recent work by the ImmunoReach network uncovered gaps in connecting concepts of metabolism and evolution in undergraduate immunology education. With these ideas in mind, we developed a comparative immunology lesson within an upper-division Animal Physiology course, in which students explore how differences in body size change both the metabolic rates and immune cell concentrations. Students who completed this activity improved their scores on scaling questions included in a class exam by more than 29% over students who only received a lecture on the course material. Pre- and post-quizzes demonstrate that the activity increased scores on questions about scaling (>17%) and immune concepts (>100%). By requiring students to apply concepts of scaling, a fundamental concept in biology and physiology, to a system not typically considered in animal physiology courses, this activity enhanced students' understanding of that topic, as well as introducing them to immune cell types. It also introduced pointillist comparative methods, just now being integrated into immune studies, thereby introducing students to leading-edge research in immunology and a new way of thinking about the immune system. We believe this approach can not only fill gaps within undergraduate immunology courses but also incorporate immunology into curricula where immunology is not a viable stand-alone course.